From dextral contraction to sinistral extension of intracontinental transform structures in the Yanshan and northern Taihang Mountain belts during Early Cretaceous: Implications to the destruction of the North China Craton. (March 2020) - Lin, Yi; Zhang, Changhou; Li, Chengming; Deng, Hongdan
Graphical abstract: Highlights: Transform systems are identified in the Yanshan and northern Taihang belts, NCC. They are the dextral contraction before 143 Ma and sinistral extension after 129 Ma. Boundaries of the modified and destructed NCC are defined by the transform systems. Transition of the transform systems marks the initiation of the destruction of NCC. Abstract: Mesozoic tectonics of the North China Craton (NCC) is characterized by craton modification and destruction that resulted in varied degrees of craton instability. The change from the end of the latest modification to the start of the final destruction of the NCC is regarded to be related to the subduction and roll-back of the Izanagi plate. However, the timing of this tectonic transition remains debated, and the extent of the area where cratonic destruction occurred is still poorly constrained. The joint part of the Yanshan and Taihang Mountain belts has been viewed as the northwest margin of the destructed eastern NCC. Detailed geological mapping and geochronological studies of this area reveal two groups of transform structures: (1) the dextral transform structures developed before 143 Ma and (2) the sinistral transform structures formed after 129 Ma. The western boundary of the dextral transform structures separate the intact NCC and the modified NCC, whereas the sinistral transform structures define the northwestern and northern boundaries of the destructed NCC. The switching from dextral to sinistral movement occurred at ca . 143–129 Ma, which is roughly coeval with the initial volcanism of the Zhangjiakou Formation, whose age becomes younger eastward. The western boundary of the sinistral transform structures migrated to the east for more than 120 km with respect to that of the dextral transform structures. These indicate that the transition from the end of the latest modification to the start of the final destruction of the NCC occurred in 143–129 Ma. In regional geology, this transition is consistent with the geodynamic setting of the transformation from the Late Jurassic flat-slab subduction to slab roll-back of the Izanagi plate since 144 Ma.